THE RACIAL FACTOR AND PAN-AFRICANISM IN NIGERIAN FOREIGN POLICY - JOHN TOR TSUWA; AFONGU AONDOAKAA IORNUMBE (International Studies Journal)
This paper assesses the racial factor and Pan-Africanism in Nigerian foreign policy. Nigeria’s effort to end racism and encourage Pan-Africanism had a very profound impact on the national liberation struggle of the African people. It has helped and indeed informed the development and articulation of a philosophy for the global engagements of the post-colonial African states. The paper adopts secondary sources of data and the role theory as a framework of analysis. The building of transnational and transcontinental solidarity among the people of African descent has been central to Nigerian foreign policy direction. The paper discovered that, Nigeria as a black nation has displayed a great commitment in the liberation struggles waged against slavery, colonialism, neo-colonialism and racist regimes in African continent such as in South Africa, Zimbabwe, Namibia among others. Again, it is important to note that, Nigeria spearheaded formation of the Organization of African Unity (now AU). The racial factor and pan-Africanism in Nigerian foreign policy proves Nigeria’s commitment to addressing the challenges of Africa as recognized by the framers of Nigerian foreign policy.  The paper recommends that, Nigerian foreign policy should seek to protect the integrity of the black man across the globe.